STUDIES OF USE HYDROGEN PEROXIDE (H2O2) OXIDIZING TO REDUCTION CYANIDE LEVEL IN WASTEWATER - Muntasir -; M. Sjahrul; Muhammad Zakir; Indah Raya (PROSIDING SEMINAR KIMIA, 2015)
Has done conducted research studies the use of oxidizing hydrogen peroxide (H2O2) to the reduction of cyanide levels in the wastewater. Parameters measured were the optimum concentration of hydrogen peroxide, pH optimum, optimum contact time between Hydrogen Peroxide with wastewater in reducing the cyanide content. Cyanide obtained from steam distillation of liquid waste and assay using 0.02 N silver nitrate. Variations in the concentration used was 100 ppm, 200 ppm, 300 ppm, 400 ppm and 500 ppm; pH variation is (7, 8, 9, 10 and 11) and the variation of contact time are: 30, 60, 90, 120 and 150 minutes. The results showed early treatment of cyanide content of 50.22% w/w and experienced a reduction after the addition of H2O2 concentration of 100 ppm, 200 ppm, 300 ppm, 400 ppm and 500 ppm; variations in pH is 7, 8, 9, 10 and 11 and the variation of contact time are: 30, 60, 90, 120 and 150 minutes. The optimum treatment is the optimum concentration of H2O2 at 500 ppm with a reduction in levels of 36.40% w/w, pH Optimum pH 8 with reduced levels of 40.91% and an optimum contact time at 60 minutes with a reduction in levels of 37.09% w/w.